Some Observations on the Perception of Muslims in 16th Century Portuguese Chronicles - Hava Önalan (İslam Tetkikleri Dergisi, 2025)
The sixteenth-century Portuguese chronicles, while narrating the Age of Discoveries in an epic tone, are also notable for their hate speech against Muslims and Islam. In these chronicles, the life of Prophet Muhammad and Islam are often depicted in a biased and disparaging manner. Portugal’s activities in India not only brought economic rivalry with Muslim states but also intensified religious conflict. Plans to destroy sacred cities of the Islamic world, such as Mecca, Medina, and Jeddah, and to desecrate Prophet Muhammad’s tomb, were documented in detail. Muslims were frequently derided with terms like “followers of Muhammad” or “adherents of a false religion”, while Mecca, Medina, and Jeddah were described as “places that must be destroyed.” In the correspondence of Afonso de Albuquerque and other Portuguese leaders, explicit plans to demolish these cities are evident. To protect its economic interests, Portugal supported conflicts among Muslim states and exploited these divisions to its advantage. Chroniclers of the period portrayed Islam as “heresy” and favored a narrative that exalted Christianity. Chronicles not only reflect Portugal’s religious and political discourses but also serve as critical documents for understanding the tense relationship between the two religions and its economic, political, and cultural contexts. This article aims to depict the Muslim-Christian conflict of the 16th century through the perspective of the Portuguese chroniclers of the period.